Genome-scale metabolic reconstructions of multiple Salmonella strains reveal serovar-specific metabolic traits - Yara Seif (Nature Portfolio, 2018)
Salmonella serovars colonize a wide range of hosts but the underlying genetic determinants remain poorly understood. Here, Seif et al. use a network-based computational analysis to link specific metabolic capabilities with host range and nutritional niche.